Co-activation of super-enhancer-driven CCAT1 by TP63 and SOX2 promotes squamous cancer progression - Yuan Jiang (Nature Portfolio, 2018)
Master regulator transcription factors TP63 and SOX2 have been reported to overlap in genomic occupancy in squamous cell carcinomas (SCCs). Here, the authors demonstrate that TP63 and SOX2 promote co-operatively long non-coding RNA CCAT1 expression through activating its super-enhancer, and CCAT1 forms a complex with TP63 and SOX2, which regulates EGFR super-enhancers and enhances both the MEK/ERK1/2 and PI3K/AKT signaling pathways in SCC.